Free radical scavenging activity, ferric reducing antioxidant power and total phenolic content of ethanolic and aqueous extracts of the bark of calabash (Crescentia cujete0. - Juanillo, Angel Ann B. (2016.)
The advent of health problems including degenerative diseases associated with the accumulation of free radicals led to researches leaning toward studying antioxidants from natural products because of its potential to combat oxidative stress. In response to this, the study aims to provide information by evaluating the antioxidant activity and the phytochemical composition of the Crescentia cujete bark. Specifically, it aims to compare the antioxidant activity of the folkloric preparation of plant decoction in traditional medicine using water as the solvent, to the laboratory method of extracting the active components by soaking in ethanol. The antioxidant properties of ethanolic and aqueous extracts of the bark of this plant were evaluated through DPPH Free Radical Scavenging Activity Assay and Ferric Reducing Antioxidant Power (FRAP) Assay and the results were compared to ascorbic acid as the positive control. The Total Phenolic Content of the bark extracts was also determined. The ethanolic extract showed more antioxidant activity than the aqueous extracts, based on lower IC50 value, higher %yield, %RSA and reducing tendencies. Statistical analysis exhibits significant difference in the results from the DPPH (p = 3.08x10-13) and FRAP (p = 0.013) assays but not in the determination of total phenolic content (p = 0.2367). qualitative phytochemical screening showed that the extracts contain tannins, flavonoids, saponins, terpenes, steroids, and alkaloids which may be responsible for the antioxidant activity of the Crescentia cujete bark.
Thesis -- Bachelor of Science in Chemistry. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Calabash, Bark (Crescentia cujete); Aqueous extracts; Antioxidant